2023
DOI: 10.1111/jnc.15959
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Neurochemistry Review: Microglial immunometabolism in traumatic brain injury

Nathan R. Strogulski,
Luis V. Portela,
Brian M. Polster
et al.

Abstract: Traumatic brain injury (TBI) is a devastating neurological disorder caused by a physical impact to the brain that promotes diffuse damage and chronic neurodegeneration. Key mechanisms believed to support secondary brain injury include mitochondrial dysfunction and chronic neuroinflammation. Microglia and brain‐infiltrating macrophages are responsible for neuroinflammatory cytokine and reactive oxygen species (ROS) production after TBI. Their production is associated with loss of homeostatic microglial function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 239 publications
(411 reference statements)
0
2
0
Order By: Relevance
“…Cell metabolism changes are also important in TBI pathophysiology 54 . Experimental studies have found reduced astrocytic malate dehydrogenase 1 (MDH1) expression in concussive TBI models 55 and increased thalamic expression in blast TBI models 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Cell metabolism changes are also important in TBI pathophysiology 54 . Experimental studies have found reduced astrocytic malate dehydrogenase 1 (MDH1) expression in concussive TBI models 55 and increased thalamic expression in blast TBI models 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation within the central nervous system (CNS) is an integral feature of neurodegenerative diseases as well as neurotrauma [1][2][3][4]. Although this inflammation may initially be beneficial, chronic neuroinflammation can escalate or worsen neuropathology and cause disease progression.…”
Section: Introductionmentioning
confidence: 99%